The essential observations for reconstructing full-depth tidal currents - Wang, Yuzhe; Zhang, Yibo; Wang, Jianfeng; Lv, Xianqing (Frontiers in Marine Science, 2022)
Based on the modal decomposition and least square method, full-depth tidal currents and corresponding internal tidal modes can be obtained from limited observations. Through a series of experiments based on direct observations at the mooring MP1 and synthetic observations at the moorings MP2 and MP3 in the South China Sea, the essential observations for reconstructing full-depth tidal currents are determined. Both observations in the upper ocean (especially near the thermocline) and deep layer (below 500 m) are essential in the reconstruction. For the upper ocean, an up-looking acoustic Doppler current profiler near the thermocline is generally essential, which can also be replaced by at least 2-4 current meters (CMs). The number of CM depends on the complexity and range of buoyancy frequency variation. For the deep layer, more observations are needed as water depth increases. The observations with the CM interval/water depth ratios about 0.2 can effectively reconstruct full-depth tidal currents below 500 m based on one barotropic mode and first three baroclinic modes. Significantly, the CMs in the middle of the deep layer are more important than those at two ends of the deep layer, which may provide more cost-effective design at a small loss of accuracy. Furthermore, the CMs with the depth interval/water depth ratios less than 1/8 in the deep layer can effectively reconstruct full-depth tidal currents with high-mode baroclinic motions.